Imprints : The Pokagon Band of Potawatomi Indians and the City of Chicago - Low, John N. (Book collections on Project MUSE., 2016)
The Pokagon Band of Potawatomi Indians has been a part of Chicago since its founding. In very public expressions of indigeneity, they have refused to hide in plain sight or assimilate. Instead, throughout the city's history, the Pokagon Potawatomi Indians have openly and aggressively expressed their refusal to be marginalized or forgotten-and in doing so, they have contributed to the fabric and history of the city. Imprints: The Pokagon Band of Potawatomi Indians and the City of Chicago examines the ways some Pokagon Potawatomi tribal members have maintained a distinct Native identity, their rejection of assimilation into the mainstream, and their desire for inclusion in the larger contemporary society without forfeiting their "Indianness." Mindful that contact is never a one-way street, Low also examines the ways in which experiences in Chicago have influenced the Pokagon Potawatomi. Imprints continues the recent scholarship on the urban Indian experience before as well as after World War II.